Fatal outcome in acute fatty liver of pregnancy and review of literature - Rani, Reena; Rathore, Asmita M.; Bhasin, Sangeeta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Acute fatty liver of pregnancy (AFLP) is an uncommon life-threatening disorder of pregnancy seen commonly in third trimester. When not diagnosed at right time it can lead to hepatic failure, encephalopathy, coagulopathy, maternal and fetal mortality. The clinical symptoms and signs are nonspecific, and it needs to be identified early in order to prevent poor outcome. The gold standard for diagnosis of AFLP is liver biopsy, which is difficult in an acute setting and in abnormal coagulation profile hence the diagnosis is usually based on clinical criteria Early termination of pregnancy and good intensive care support are the mainstay of management. The authors here presented a case report where even early delivery and good critical care failed to prevent maternal mortality. Review of literature regarding etiopathogenesis, management and recurrences of AFLP are also discussed.